El tratamiento del léxico especializado en la lexicografía española del siglo XIX - Contreras Izquierdo, Narciso Miguel (Acta Hispanica, 2008)
The lexicographical treatment of the specialized lexicon of a language is one of the most serious problems lexicographers and specialists in the discipline must face; the author also affirms that it is one of the great pending tasks of Spanish lexicography. The paper proposes to examine the evolution and characteristics of the Spanish lexicographic tradition in general, and to present the different tendencies in the treatment of the lexicon specialized in the 19th century.